Evaluation of sperm integrin α5β1 as a potential marker of fertility in humans - Vernaz, Zoilo José (2022)
Sperm selection for assisted reproduction techniques is generally based on basic parameters, while key aspects of sperm competence and its journey from the deposition site to the fertilization site are overlooked. Consequently, identifying molecular markers in spermatozoa that can efficiently predict the fertility of a semen sample could be of great interest, particularly in cases of idiopathic male infertility. When spermatozoa reach the female reproductive tract, it provides to them the cellular and molecular microenvironment needed to acquire fertilizing ability. In this sense, considering the role that integrin α5β1 of spermatozoa plays in reproduction-related events, we investigated the correlation between the subcellular localization of sperm integrin α5β1 and early embryo development outcome after in vitro fertilization (IVF) procedures in human. Twenty-four semen samples from normozoospermic men and metaphase II (MII) oocytes from healthy women aged under 38 years, from couples who underwent IVF cycles, were used in this work. Sperm α5β1 localization was evaluated by immunofluorescence assay using an antibody against integrin α5 subunit. Integrin α5β1 was mainly localized in the sperm acrosomal region (45.33±7.89%) or the equatorial segment (30.12±7.43%). The early embryo development rate (data obtained from the Fertility Center) correlated positively with the localization of α5β1 in the acrosomal region (number of usable embryos / inseminated oocytes: ρ = 0.75; p<0.01 and number of usable embryos/total number of two pronuclear zygotes: ρ = 0.80; p<0.01). However, this correlation was not significant when the equatorial segment mark was evaluated. In addition, human sperm released from co-culture with bovine oviductal epithelial cells (BOEC) showed a significant enrichment in the acrosomal localization pattern of α5β1 compared to those sperm that were not co-cultured with BOEC (85.20±5.35% vs 35.00±17.09%, respectively, p<0.05). In conclusion, the evaluation of sperm integrin α5β1 immunolocalization could be a useful tool to select sperm with fertilizing ability from human semen samples before IVF procedures.